Theological Foundation toward Industri 4.0: Batik Experience in Pekalongan City - Susminingsih Susminingsih; Imam Kanafi (Ijtimā`iyya: Journal of Muslim Society Research, 2019)
The purpose of this paper is to analyze the theological foundation in the development of batik industry. The type of this research is field research, and using the qualitative perspective. The population of enterpreneur in Pekalongan City takes in such proportion, which represents the presence of each level and variants of business community. The snowball analysis model was applied here. Triangulation technique used in order to make sure the reliability of data or sources. The research found that: 1) Batik industry also determined their understanding of human nature. The awareness that human beings should be strive and even, if it is necessary, to innovate by developing the motifs, and models of their batik products as adaptation behavior to industry revolution 4.0. 2) The common theological foundation to batik experience are: human is a creature endowed with reason, human is a creature whose have feelings, human existence is characterized by consciousness in behaving. 3) The decision making in maintaining the batik industry is also driven by transcendence factors. 4) Business situations make the informants constantly looking for mutually beneficial solutions for personal, family, work-relations, government, and the environment.